2011
DOI: 10.1038/ejhg.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of H19 methylation in control and abnormal human embryos, sperm and oocytes

Abstract: ART is suspected to generate increased imprinting errors in the lineage. Following an intra cytoplasmic sperm injection (ICSI) procedure, a certain number of embryos fail to develop normally and imprinting disorders may be associated to the developmental failure. To evaluate this hypothesis, we analysed the methylation profile of H19DMR, a paternally imprinting control region, in high-graded blastocysts, in embryos showing developmental anomalies, in the matching sperm and in oocytes of the concerned couples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 25 publications
5
42
1
1
Order By: Relevance
“…In contrast to our results and the aforementioned studies [21,33] , Chen et al [27] reported higher degree of DNA methylation (49.4%±9.7% as compared to our value 37.85±4.87%) in human embryos. However, the main difference between our study and Chen et al, The number of clones is shown in the raw of "Seq.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to our results and the aforementioned studies [21,33] , Chen et al [27] reported higher degree of DNA methylation (49.4%±9.7% as compared to our value 37.85±4.87%) in human embryos. However, the main difference between our study and Chen et al, The number of clones is shown in the raw of "Seq.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation, to a certain degree, is in concordance with a previous report from the Lefèvre group [21] . Using genome-wide analysis of DNA methylation of early human blastocyst embryo, Okae et al [33] also reported an average of methylation levels with a median of around 40% for gDMRs, which is close to the value reported in this study and Lefèvre group's study [21] . It is important to note that Okae and colleagues [33] did not specifically report the methylation level of ICR1.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations